Phylogenomics of Olmeca, a Neotropical woody bamboo, based on nuclear single nucleotide polymorphism (SNP) data - Eduardo Ruiz-Sanchez; Carlos A. Maya-Lastra (Botan‪ical Sciences)
Background: The genus Olmeca comprises five species, two of which produce bacoid caryopses, while the rest produce typical caryopsis fruits. Olmeca species have a collective geographical distribution in Mexico and Honduras. Previous studies have suggested the potential monophyly of this genus based on plastid markers, but with inconclusive internal phylogenetic resolution.